2019
DOI: 10.3390/su11216097
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Drivers of Irrigator Mental Health in the Murray–Darling Basin, Australia

Abstract: There has been little work conducted on how landholders’ farm management approaches and financial capital (specifically (i) farm method such as organic farming and (ii) financial profitability) may impact mental health. In particular, there is emerging evidence that an increase in natural farm capital and environmental conditions may improve farmers’ wellbeing. We used a 2015–2016 survey, which randomly sampled 1000 irrigators from the southern Murray–Darling Basin, to model the drivers of irrigators’ psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Similar self-reported questionnaire survey by Khan et al [184] on 200 conventional and 157 organic farmers in Indiana, USA, found conventional farmers demonstrated a significantly higher frequency of neurological symptoms and depression problems. Similar results were found in Australian irrigation [182]. However, Brigance et al [185] indicated that some of the risk factors that affect the mental health of organic farmers—e.g., economic insecurity, long hours of work, social isolation, and unpredictable weather conditions—are the same as the mental risk factors for conventional farmers.…”
Section: Systematic Review Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Similar self-reported questionnaire survey by Khan et al [184] on 200 conventional and 157 organic farmers in Indiana, USA, found conventional farmers demonstrated a significantly higher frequency of neurological symptoms and depression problems. Similar results were found in Australian irrigation [182]. However, Brigance et al [185] indicated that some of the risk factors that affect the mental health of organic farmers—e.g., economic insecurity, long hours of work, social isolation, and unpredictable weather conditions—are the same as the mental risk factors for conventional farmers.…”
Section: Systematic Review Resultssupporting
confidence: 69%
“…The association with farm type (system used—such as organic farming and industry type) was also a considerable focus in the literature [182]. A study on comparing the self-reported psychological health of workers on organic and conventional horticultural farms by Cross et al [183] showed no significant difference.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct measurements of environmental variables were the most common method for environmental measurement and were found in drought, noise, and pollutant studies: In drought studies, rainfall data were collected alone [ 66 , 67 ] or in combination with: drought period [ 68 ], soil moisture [ 68 ], or water allocations [ 68 ]. These data could also be combined to create Hutchinson’s Drought Index [ 65 , 108 , 109 ]. Noise monitoring was carried out using static noise monitors at the neighbourhood scale [ 69 , 71 , 72 , 73 , 74 , 78 , 110 , 111 , 112 , 113 ], recording peak and off-peak noise at varied locations to map noise across the study sites.…”
Section: Results (Step 5) Including Expert Consultations (Step 6)mentioning
confidence: 99%
“…In drought studies, rainfall data were collected alone [ 66 , 67 ] or in combination with: drought period [ 68 ], soil moisture [ 68 ], or water allocations [ 68 ]. These data could also be combined to create Hutchinson’s Drought Index [ 65 , 108 , 109 ].…”
Section: Results (Step 5) Including Expert Consultations (Step 6)mentioning
confidence: 99%